The criteria for self determination and recognition as a sovereign state: Case of Kosovo - Siboe, Nancy Namisi (Open Science Journal, 2020)
Self-determination is a controversial issue in public international relations as well as in international law. The rise of groups of people in different geographical locations of the world, seeking alienation and recognition, as independent sovereign state cannot therefore continued to be ignored. The protection of the inviolable right of state sovereignty as provided for under the preamble of the United Nations Charter cannot be shoved under the carpet. It is now a public debate on whether state sovereignty has to be protected at all costs including ignoring pressure from proponents of self-determination. What then are the characteristics or criteria that qualifies a group to be entitled to secession? The aim of this article is to look at the brief history of self-determination and assess the criteria considered for declaration of sovereignty. The case of Kosovo will be considered extensively. The author seeks to fill the gap in existing literature on whether recognition automatically confers upon meeting the laid down requirements or political decisions also hold water. The methodology used is theoretical It is clear from the results that the subject of graduation from self-determination to state sovereignty is an issue not so much of legality but political recognition by the international community. This research will positively contribute to the debate surrounding self-determination and sovereignty. It will at least demystify the fog surrounding this highly contested principle. The research will help in widening the criteria for state sovereignty to include political recognition. The author proposes more studies in the area of whether political recognition is legal when making international law decisions.